Business fixed investment: evidence of a financial accelerator in Europe - Philip Vermeulen (European Central Bank (ECB), 2000)
Financial accelerator theories imply that weak balance sheets can amplify adverse shocks on firm investment. This effect should be asymmetric, stronger in downturns than in upturns and stronger for small firms than for large firms. This paper provides empirical evidence of the presence of a financial accelerator in the four largest euro area economies: Germany, France, Italy and Spain. Using annual firm balance sheet data over the period 1983 - 1997 it is shown that weak balance sheets are more important in explaining investment during downturns than during upturns. It is further shown that the effects of the accelerator are largest for small firms.
Keywords: E22; E44; 330; business fixed investment